Nuevos caminos de redención en el Antropoceno - Gatti Riccardi, Giuseppe (Verba hispanica, 2024)
There are many examples present in contemporary literature that propose an ultra-pessimistic reading of destructive human action. These are texts that: a) enshrine an ideology of defeatism, constructing dystopian scenarios in which globalized systemic violence is present, or b) propose characters who renounce any attempt at a reaction, accepting their own impossibility of acting. In contrast to fiction of this nature, which advocates reflection on the impossibility of salvation for the planet and its inhabitants, our purpose is to analyze the literary work of those Uruguayan writers who care about repre-senting the idea of a path that is still possible. The article explores contemporary stories that challenge the dystopian defeatism traditionally associated with environmental literature and propose more resilient alternatives to the ecological crises of the Anthropocene.
Keywords: 21 st.; distopični defetizem; dystopian defeatism; hibridizacija; hybridization; interspecies dialogue; medvrstni dialog; transcorporality; transtelesnost; Uruguayan literature; urugvajska književnost